2021
DOI: 10.1186/s12889-021-11295-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on stress, mental health and coping behavior in German University students – a longitudinal study before and after the onset of the pandemic

Abstract: Background The COVID-19 pandemic has led to massive restrictions in public and private lives, including a shut-down of face-to-face teaching at universities in Germany. We aimed to examine the impact of these changes on perceived stress, mental health and (study-)related health behavior of students in a longitudinal study. Methods For two timepoints – the year before the COVID-19 pandemic (2019, n = 1377) and the year during the COVID-19 pandemic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 42 publications
5
93
1
4
Order By: Relevance
“…Descriptive analysis of the data shows that students are generally moderately satis ed with their lives, although 38.5% show rather poor general health. This stands in contrast to the longitudinal study of Voltmer et al [13] reporting that 77% of the students rated their health as (very) good in June 2020. During corona, about one in ten students suffered severe nancial losses, and both the impairment and the burden can be considered severe.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Descriptive analysis of the data shows that students are generally moderately satis ed with their lives, although 38.5% show rather poor general health. This stands in contrast to the longitudinal study of Voltmer et al [13] reporting that 77% of the students rated their health as (very) good in June 2020. During corona, about one in ten students suffered severe nancial losses, and both the impairment and the burden can be considered severe.…”
Section: Discussioncontrasting
confidence: 90%
“…Accordingly, Kohls et al [5] showed that in July and August 2020 during the pandemic 37% of the students (n = 3,382) were affected by depressive symptoms according to the PHQ-9 showing an increase compared to numbers before the pandemic. The German longitudinal study of Voltmer et al [13], however, found no signi cant differences in general health, stress, as well as depression symptoms and only a minor elevation of anxiety between 2019 and 2020 (June) in their student sample.…”
Section: Introductionmentioning
confidence: 76%
“…Females tend to be more predisposed to express their feelings and are more likely to experience different social expectations, pressures, and gender equalityrelated positions [23]. However, other studies did not confirm this trend [13,14,16,26].…”
Section: Introductionmentioning
confidence: 93%
“…In fact, various studies have consistently showed an increase in anxiety and stress symptoms associated with the COVID-19 pandemic among medical students [12][13][14][15][16][17][18][19][20][21][22][23][24] as well an increase in depressive symptom [15,17,21,22,24,25]. The factors attributable to the pandemic explaining anxiety and depression may be due to being afraid of getting the infection and the risk of the development of severe illness and complications [26]. On the other hand, some studies showed that living in urban areas, living with parents, having economic stability, having social support and being younger appeared to be protective factors for depressive symptoms [13,16,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation